WOMEN'S LEADERSHIP IN INDONESIA CONTEMPORARY FIQH PERSPECTIVE - Hamka, Hamka; Misbahuddin, Misbahuddin; Aidid, Hasyim; Satriani, Indra; Syamsuddin, Syamsuddin (Jurnal Diskursus Islam, 2021)
This paper describes the leadership of women in Indonesia in contemporary fiqh. The method used is literature and describes the main problems in the research. The sub-problems that are addressed are the role of women in the era of the Prophet and contemporary fiqh in women's leadership in Indonesia. This study found that the involvement of women in the time of the Prophet was not restricted in social aspects, attending lectures, discussion partners and so on. Reflecting that social involvement in the Sasulullah era was very open to women, it is not appropriate and fair if women are limited in their space of movement in social participation or career. The paradigm of women "staying at home" is not in line with the Prophet's example in his time, especially in today's life, especially in Indonesia, which gives women the freedom to work. The explanations in the collective verses of the Qur'an and Hadith and social facts at the time of the Prophet, as well as historical facts in Indonesia, are evident in the involvement of women in all aspects, including being leaders in social, educational and political aspects. Women's political participation is in line with Indonesia's social and constitutional situation in opening up space for women to be involved in practical politics, including running for Regional Head and President. The potential of women in terms of leading the state (becoming heads of state) is very open and justified in Islam because no text contradicts contextually but provides the same rights and responsibilities as men in all aspects, including religion, social and culture. Political.